79 SIMULATION-BASED MEDICAL EDUCATION: A 'HIP' WAY TO LEARN ABOUT ORTHO-GERIATRICS!. (18th November 2021) - Murphy, B; Laffan, S; Sullivan, S O; Ballester, G W; Meagher, M K; Noone, I; Cassidy, T; Murphy, T; Cooke, J; Pope, G; Mulcahy, R; O'Regan, N
Abstract: Background: Simulation-based medical education (SBME) is emerging as a key method of medical education, particularly in the setting of the COVID-19 pandemic. As part of a simulation development competition (SimStars) run by the National Doctors Training and Planning Unit and the South–South West Hospital Group, we brought together an inter-disciplinary team to develop a simulation scenario on hip fracture. Methods: Our development team consisted of members of the Geriatric Medicine and Orthopaedic Departments. We developed a scenario that can be adapted to suit the needs of learners in orthopaedics, medicine, or nursing. We ran the simulation on a medical ward with one candidate and four facilitators from the Geriatric Medicine Department. The candidate (medical SHO) was presented with a patient (facilitator one), who had sustained a hip fracture following a fall. The candidate was directed to elicit a falls and bone health history, screen for delirium, and suggest further investigations and management. Subsequently, feedback was sought from all participants. Results: The simulation took twenty minutes, debriefing took fifteen minutes. All considered, the simulation an enjoyable and feasible method for teaching and learning, and a novel way to promote team-building. The candidate felt competent in some areas, reporting that the scenario provided positive reinforcement. She reported feeling supported in identifying areas for further learning. The facilitators also considered this method a useful way to highlight a candidate's learning needs and direct further teaching. The candidate requested further SBME-based sessions. Conclusion: This SBME session in Ortho-Geriatrics was well-received by the candidate and facilitators. All participants enjoyed teaching and learning through this medium. Areas of high competency were reinforced and areas for future learning were identified. Further SBME was requested across more topics and for simulation training to be brought in as part of formal training.